REFORMASI SISTEM PERADILAN PIDANA DALAM RANGKA PENANGGULANGAN MAFIA PERADILAN - Widodo, J. Pajar (Jurnal Dinamika Hukum, 2012)
The purpose of reformation criminal justice system is to strengthen the principle of independence and impartiality criminal justice. Strengthening of independence principle and impartiality criminal justice is done in the process of constitutional amendment and legislation. The reformation of the criminal justice system includes the substance of the law of one roof system design of judicial power that culminated in the Supreme Court. The strengthening of the principle of independence and impartiality criminal justice is to overcome judicial mafia practice that equipped by law reformation culture to uphold the value system, which are values and principles due process of law. Keyword: Judicial reform, independence, judicial mafia